Dosis de bioestimulante tetrahormonal en el cultivo de lechuga (lactuca sativa l.) variedad great lakes 659 bajo condiciones agroecológicas del distrito de lamas - Gebol Reátegui, Yaneth (2012)
Lettuce (Lactuca sativa L.) is the most important group of plant leafy vegetables; consumed in salads, is widely known and is grown in almost every country in the world and has a great diversity due mainly different types of leaves and growth habits of plants. The production, marketing and consumption of lettuce growing in the world are increasing day and represent a very significant support in the agricultural economy of the producer and the improvement of the health of consumers around the world (Aranceta and Perez, 2006 ). Crop production Lettuce nationwide planted and harvested every month of the year and according Angulo (2008), production increased from 2005-2007, the values ​​were 30.95, 33.53 and 34.04 respectively (thousand metric tons). The limitations of culture at national level in relation to the performance decrease the incidence of pests and diseases (Liriomyza trifolii, Liriomyza huidobrensis, Trialeurodes vaporariorum, Bremia lactucae, Sclerotinia sclerotiorum, Rhizoctonia, Fusarium, Pythium) and the climate variability. The real possibility of getting good returns, only we can achieve through proper and balanced nutrition according to present requirements during crop development and the implementation of growth-regulating substances of natural or synthetic origin, which cause and support the achievement of the expected changes in the different phenological stages of crops and plants that often do not show themselves to their full potential for development and production, due to the variability of soil, and frequent and common changes temperature, radiation, wind and humidity present in field conditions during the crop development, as well as the changes caused by the attack of pests, diseases and weed competition, among other factors, which often vary the speed and normality growth and development of crops. The demand for healthy food and high quality is increasing, and the volumes and characteristics of the products are fully linked to good nutrition of the plant and the possibility that the features and fully express their genetic potential, in the best environmental conditions and management for development. In the department of San Martin, specifically in the district of Lamas, since warmer weather is encouraging the cultivation of lettuce with the variety Great Lakes 659, still according Gebol (2010), is a variety that retains its characteristics and strategies of adaptation to the ecological conditions of district Lamas; why through this work is to assess their intrinsic potential relative to its performance using five doses of Biostimulant tetrahormonal Biogyz.